Overweight and Obesity Are Increased in Childhood-Onset Cerebrovascular Disease. (April 2013) - Pearson, Virginia; Ruzas, Chris; Krebs, Nancy F.; Goldenberg, Neil A.; Manco-Johnson, Marilyn J.; Bernard, Timothy J.
The objective of this work was to determine whether overweight/obesity is a risk factor for cerebrovascular disease in children. The study included 53 children with non–neonatal-onset cerebral sinovenous thrombosis or arterial ischemic stroke. The prevalence of overweight/obesity was compared between this cohort and healthy children from the National Health and Nutrition Examination Survey. In addition, cerebral sinovenous thrombosis patients were compared to a group of matched hospitalized controls. The prevalence of overweight/obesity was significantly higher in the cerebral sinovenous thrombosis cohort (55%), but not the arterial ischemic stroke cohort (36%), relative to national controls (32%; P = .04 and P = .81, respectively). Similarly, the prevalence of overweight/obesity was significantly higher in the cerebral sinovenous thrombosis cohort than in Colorado controls (25%; P = .02). In conclusion, the prevalence of overweight/obese was significantly increased in cerebral sinovenous thrombosis patients as compared to both national and local controls. Results should be evaluated in a larger multi-institutional cohort.